STUDI EKONOMI TEKNIK PEMBUATAN PERAHU CADIK JENIS BOTTOM GLASS DARI BAHAN FIBER GLASS UNTUK WISATA BAHARI DI KELURAHAN BANTEN KECAMATAN KASEMEN KOTA SERANG PROVINSI BANTEN - Sri Sulasminingsih; Budiman Adi Setyawan; Amir Marasabessy (Bina Teknika, 2017)
The fishermen in Kasemen subdistrict are the traditional fishermen who depend on the stars in the sky for navigation in caching fishes at the ocean . So, they do not go to the ocean everyday. There are many days that they must stay at home. They have another skill besides the fishermen. That is a problem. A solution of this problem is producing a special boat for the ocean tourisme. The boat is katir boat that made from plastics and combine with the glass at the bottom to see the beautiful under water views. The fishermen could be the guide of the sea tourisme because this area is rich with life and under water views. For the first , study to calculate of the cost is to be done , make a design of katir boat with the glass on the bottom and steps of production with economy of engineering method. The results are if the fishermen have to make the boat (Katir) with a special type by themselves need a lot of cost Rp.11.500.000 by a boat (without the engine) . If  the owner of the boats want to make of Katir production from fiberglass with a glass on the bottom as a special type for the ocean tourisme make a lot of cost Rp.12.710.000 by a boat (without the engine)  and get a Rp.1.110.000 profit  after reduced by production cost Rp.11.600.000 by a boat. If the investors want to enter the bussiness of  Katir industry seriously , the capital will be back (Break Event Point/BEP) on time of 4.5 years or after 10th Katir production.